Association of Psychosocial Symptoms, Blood Pressure, and Menopausal Status in African-American Women. (October 2020) - Still, Carolyn H.; Tahir, Sadia; Yarandi, Hossein N.; Hassan, Mona; Gary, Faye A.
African-American women have disproportionate rates of hypertension that can be further complicated as they transition through menopause. Stress, coupled with depression and hypertension in perimenopausal African-American women has not been fully explored. This study examines the associations of stress, depression, and social support on systolic blood pressure (SBP) among a sample of 184 perimenopausal African-American women. We used descriptive statistics, Pearson's correlation, and logistic regression to analyze data stratified by menopausal status (perimenopausal or menopausal) and SBP status (<130 mmHg vs. >130 mmHg). Women classified as menopausal reported higher levels of stress and depressive symptoms, and lower levels of social support. Age, body mass index (BMI), health insurance, and perceived health status were significant predictors of SBP in menopausal women. Stress, depression, and social support did not play a role in SBP. It is necessary that future research focus on reducing cardiovascular risk include addressing menopausal health.